Acute Decompensated Heart Failure in Patients With and Without COVID-19 - The Experience of a Romanian Center - Vintilă Ana-Maria; Horumbă Mihaela; Miron Paul; Balan Răzvan; Catrangiu Maria-Beatrice; Negoescu Iris-Andreea; Trifan Iuliana; Vintilă Vlad-Damian; Gurghean Adriana; Săvulescu-Fiedler Ilinca (Sciendo, 2022)
Our goal was to characterize a cohort of heart failure patients with and without COVID-19 in terms of demographics, comorbid conditions, treatment regimens, lab test results and outcome.